Straw Incorporation Effects on Net Photosynthetic Carbon Assimilation and Maize Growth - Wang, Xin-Xin; Li, Jiaqi; Wang, Danlei; An, Tingting; Qin, Wei; Zou, Hongtao; Rengel, Zed (Frontiers in Agronomy, 2022)
Returning straw into soil could increase soil organic carbon (SOC) and promote crop growth. However, little has been reported on the source of C for increased SOC (straw C or crop photosynthetic C). To investigate the assimilation of photosynthetic C and its distribution in soil in the maize growth season, we set up a one-year 13C pulse-labelling experiment in a consecutive maize-straw-returning long-term trial. Four treatments were included: no straw return (control), straw mulching on the soil surface (cover), return in 0-20 cm layer (shallow) and 20-40 cm layer (deep). We found that the deep straw incorporation significantly (P<0.05) increased maize 100-grain weight (by 7.8%), yield in the coming year (by 10.5%) and SOC (by 13.4%), compared with the control. During the growing season, the deep straw incorporation increased photosynthetic 13C assimilation in shoots by 17.4% and the partitioning of photosynthetic 13C to soil by 7.9% at early jointing, and by 11.5% at maturity. The contribution of photosynthetic C to microbial biomass C (MBC) and dissolved organic C (DOC) was highest at jointing, and at harvest amounted to 39.1 % of MBC and 28.8% of DOC. The results highlighted the importance of regulating the soil carbon dynamics via the deep straw return strategy. In conclusion, deep straw incorporation significantly increased photosynthetic efficiency and facilitated partitioning of photosynthetic C to roots and soil, thus promoting maize growth and yield.